ACUTE RESPIRATORY INFECTIONS PREVENTION AND TREATMENT IN CHILDREN - F.S. Kharlamova; O.V. Kladova; V.F. Uchaikin; T.P. Legkova; L.I. Feldfiks (Union of pediatricians of Russia, 2009)
The article examines the aspects of clinical efficacy in prevention and treatment of acute respiratory infections and influenza by Arbidolum with direct anti-virus and indirect immunostimulating and interferon inducing effects. It outlines the results of various research studies that have proved the soundness of its application. A study involving 500 children that was conducted at the State Educational Institution of Higher Professional Education Russian State Medical University has proved the economic efficiency of regiments for treatment and prevention of ARI using this medication in sickly and chronic children.Key words: Arbidolum, antiviral agent, sickly children.